2004
DOI: 10.1038/sj.npp.1300393
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Improves Sustained Attention in Mice: Evidence for Involvement of the α7 Nicotinic Acetylcholine Receptor

Abstract: In humans, nicotine has been shown to improve attention in both normal and impaired individuals. Observations in rats reflect some, but not all aspects of the nicotine-induced improvements in humans. To date these findings have not been replicated in mice. To examine the effect of nicotine on sustained attention in mice, we have established a version of the 5-choice serial reaction-time (5-CSR) task with graded levels of difficulty, based upon spatial displacement and a variable intertrial interval. Using this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
178
4
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(201 citation statements)
references
References 56 publications
(91 reference statements)
17
178
4
2
Order By: Relevance
“…Various paradigms have been developed to assess similar learning and memory, and attention functions in rodents and similar to what is seen in humans, nicotine has been shown to improve rodent deficits in these paradigms [105,106,107,108,109]. DMXBA improves monkey performance on a delayed matching to sample task, an effect that persists for 24 hours after drug administration [110].…”
Section: Dmxba As a Prototype Drugmentioning
confidence: 99%
“…Various paradigms have been developed to assess similar learning and memory, and attention functions in rodents and similar to what is seen in humans, nicotine has been shown to improve rodent deficits in these paradigms [105,106,107,108,109]. DMXBA improves monkey performance on a delayed matching to sample task, an effect that persists for 24 hours after drug administration [110].…”
Section: Dmxba As a Prototype Drugmentioning
confidence: 99%
“…Despite the importance of the α7 nAChR subunit, its deficiency results in viable, anatomically normal α7-null mice (Orr-Urtreger et al 1997;Paylor et al 1998). The only abnormal CNSrelated phenotypes reported in these mice were mild cognitive deficits (Young et al 2004(Young et al , 2007 and reduced nicotine withdrawal symptoms (Salas et al 2007). It has been suggested that overexpression of other types of nAChRs compensates for the depletion of α7-nAChRs, and in fact, the upregulation of α3 and α4 nAChR subunits was demonstrated in brains of postnatal α7−/− mice (Yu et al 2007).…”
Section: Discussionmentioning
confidence: 94%
“…The normal ageing process in humans is associated with impairments in sustained attention 50,51 and similar age-related deficits have been detected in rats using the 5-CSRTT. 39,52,53 Although this test has been used in mice, 54,55 no ageing studies have previously been reported. Interestingly no age-related deficit was found in either the transgenic or WT mice and all ages of mice performed the task equally well.…”
Section: Discussionmentioning
confidence: 99%
“…Retraining began with the 10 s stimulus duration and decreased to 2 s as previously described. 55 Therefore, asymptotic performance was assessed when mice were 14-, 20-and 27-month old. Group sizes reduced slightly over time: n ¼ 6 and 5 for transgenic and WT mice, respectively, at 20 months and n ¼ 3 per group at 27 months.…”
Section: Western Blotting Analysismentioning
confidence: 99%